Objective Necessity and Freedom in Man’s Conscious Activity - Jurkūnaitė, Gema (Problemos, 1973)
An absolute contraposition of necessity to freedom, of the object to the subject, resulting from the contemplative methodology, has determined the idealistic methodology and the evaluative descriptive nature of views on the history of society. Hegel was the first to reject the unfounded contraposition of an absolute freedom and objective necessity. The unity of the subjective and the objective is disclosed in practical activity. Yet, according to Hegel, the genuine subject of the practical activity is not man but an objectivised idea. Contrary to Hegel, Marx proceeds from the real subject and goes on to its objectivisation in history which is regarded as a result of man’s practical activity. According to Marx, activity is concrete, sensual practice through which the unity of the object and the subject is manifested. Thus both objectivity and subjectivity are immanent in man’s activity and are formed in the course of this activity. When the expedience of man’s activity is viewed as a condition for achieving certain results, there is no need in contraposing deterministic and teleological principles in the studies of social development.